2018
DOI: 10.1177/0018720818800538
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Adaptations to Lane Keeping Systems: Effects of Exposure and Withdrawal

Abstract: Objective: A driving simulator study was conducted to evaluate the longitudinal effects of an intervention and withdrawal of a lane keeping system on driving performance and cognitive workload. Background: Autonomous vehicle systems are being implemented into the vehicle fleet. However, limited research exists in understanding the carryover effects of long-term exposure. Methods: Forty-eight participants (30 treatment, 18 control) completed eight drives across three separate days in a driving simulator. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…However, the standard deviation of lane position increased over the same period, possibly indicating a reduction in driver performance. This is in agreement with Miller et al (2019) who found an increase in SDLP after using an LKS. Overall because improvements in driver performance between the practice and final drives were demonstrated for most measures and changes in driver performance due to LKAS alignment errors moved opposite to those improvements, the experimental design was effective.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, the standard deviation of lane position increased over the same period, possibly indicating a reduction in driver performance. This is in agreement with Miller et al (2019) who found an increase in SDLP after using an LKS. Overall because improvements in driver performance between the practice and final drives were demonstrated for most measures and changes in driver performance due to LKAS alignment errors moved opposite to those improvements, the experimental design was effective.…”
Section: Resultssupporting
confidence: 93%
“…Some researchers have investigated full Lane Keeping Systems (LKS), which, opposed to a LKAS, provides enough torque to steer without any driver intervention. Miller et al (2019) conducted an experiment to investigate what happens when the LKS functions stop with a resulting transition from automated driving to manual driving. They found that drivers had an increased SDLP and decreased mean Time to Collision (TTC) after system withdrawal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An unexpected finding in our study was that mean headway was not affected by driving condition nor secondary task difficulty. However, previous work (Miller & Boyle, 2018) that examined the effects of LKS and secondary task on workload and driving performance, found shorter headway times using the LKS and in the Manual driving condition without a secondary task. In another study, Kubose (2005) reported longer headway times in the dual-task condition (driving with a speech task) compared to the single-task condition.…”
Section: Discussionmentioning
confidence: 80%
“…For example, for Level-1 automation, Rudin-Brown and Parker (2004) showed that the use of ACC alone results in significantly larger variability in lane position compared to manual driving. Miller and Boyle (2018), on the other hand, reported that the introduction of LKS in isolation reduces mean headway distances.…”
Section: Introductionmentioning
confidence: 99%
“…As a feasible transition for automated driving at the present stage, cooperative driving possesses vital academic value. Meanwhile, cooperative driving for lane keeping has been developed to reduce the driver's workload and satisfy driver intentions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%